Analysis of American slang words in Whiplash movie - Sotyarini, Ririn (Linguistics Initiative, 2025)
This paper examines the linguistic and functional characteristics of American slang within the film script of Whiplash (2014), written by Damien Chazelle. It categorizes slang based on linguistic features and discusses their roles in portraying character relationship, emotional intensity, and group-based identity in a high-pressure music academy setting. The study finds that slang in Whiplash functions not just as informal language, but as a purposeful communicative strategy. It facilitates peer interaction, expresses strong emotion, and strengthen group identity, while also serving as a tool for social division, pressure, and control. These expressions reflect a range of linguistic features – such as ellipsis, rhythm, creativity, vulgarity, and ephemerality – that mirror the demanding environment of competitive jazz. Ultimately, the film demonstrates how slang can function as both a bonding mechanism and a form of domination, highlighting the powerful relationship between language, power, and identity.